Environmentally Friendly Extraction of Salam Leaves Using the Ultrasound-Assisted Extraction and Evaluation of Their Antioxidant Potential - Panji Setya Amitra; Alimuddin; Anton Irawan (Tecno Scientifica Publishing, 2026)
Salam leaves (Syzygium polyanthum) have been found to contain phenolic compounds that exhibit significant antioxidant potential. The objective of this study was to ascertain the impact of varying methanol-water solvent ratios on the extraction yield, total phenolic content, and antioxidant activity of salam leaf extract through the utilization of the UAE method. The extraction process was executed using methanol–water solvent ratios of 9:1, 8:2, 7:3, 6:4, and 5:5 (v/v). The total phenolic content was determined using the Folin–Ciocalteu method. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay based on IC50 values. The findings indicated that the extraction yield reached its zenith at a 9:1 ratio (12.4%) and attained its nadir at a 5:5 ratio (2.7%). TPC increased with higher water content, reaching a maximum of 12.264 ± 0.114 mg GAE/g extract at a 5:5 ratio. The strongest antioxidant activity was observed at 9:1 (IC50 = 47.109 ± 0.457 ppm), while the weakest was at 5:5 (IC50 = 74.300 ± 0.945 ppm). The findings demonstrate that UAE in combination with the optimisation of methanol:water solvent enables the extraction of phenolics and antioxidant activity to be tuned. The optimized UAE conditions offer a green, efficient, and practical approach for producing antioxidant-rich extracts from S. polyanthum, with potential applications in the food, nutraceutical, and natural product industries.